Analysis of current legislation concerning the alienation of land - Хом’яченко, Світлана Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article deals with the changes in the legislation on the alienation of land for public purposes and for reasons of social necessity. Implemented characteristics of these relationships and their analysis